2018
DOI: 10.3390/ijerph15020271
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study on the Sustainability of China’s Grain Quality Improvement: The Role of Transportation, Labor, and Agricultural Machinery

Abstract: As a major part of farming sustainability, the issues of grain production and its quality improvement have been important in many countries. This paper aims to address these issues in China. Based on the data from the main production provinces and by applying the stochastic frontier analysis methodology, we find that the improvement of transportation and the use of agricultural machinery have become the main driving forces for grain quality improvement in China. After further studying different provinces’ pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This process should take the impact of globalization on sustainable development and environmental policies into account. In China, for example, the twelfth Five-Year Plan shifted R&D priorities from renewable energy to pollution control and other sustainable green technologies [13,39,40]. However, the proposed approach limited by the baseline data, which allow for the macro-level assessment only.…”
mentioning
confidence: 99%
“…This process should take the impact of globalization on sustainable development and environmental policies into account. In China, for example, the twelfth Five-Year Plan shifted R&D priorities from renewable energy to pollution control and other sustainable green technologies [13,39,40]. However, the proposed approach limited by the baseline data, which allow for the macro-level assessment only.…”
mentioning
confidence: 99%
“…With the development of agricultural mechanization, however, China has explored its own road to mechanization.China's agriculture has experienced a large expansion of machine investments by farmers and machine rental services provided by specialized agents, which has contributed to the mechanization of agricultural production [4][5][6]. Previous literature on the agricultural mechanization in China has concluded that the agricultural mechanization has increased the grain yield and ensured food security in China [7][8][9]. At present, the agricultural mechanization in China is in the transition period from whole process mechanization to comprehensive mechanization [10].…”
mentioning
confidence: 99%
“…A wide range of sustainable development issues have been addressed such as: To satisfy human needs for sustainable development, many constraints concerning natural resources and environment must be accounted for. According to the data from the main food production provinces, Zhang et al [ 5 ] adopted a stochastic frontier analysis methodology to study sustainable development of food quality in China. Taking regulation as a mean to reducing negative externality and enhancing positive externality, Wang et al [ 6 ] proposed an improved ordering preference method with entropy weight and Mahalanobis distance (E-M-TOPSIS) to conduct a performance evaluation of China’s energy regulation.…”
Section: About the Papers Of This Special Issuementioning
confidence: 99%